1977
DOI: 10.1093/bja/49.6.525
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Morphine With Naloxone in Dogs: Cardiovascular Effects With Special Reference to the Coronary Circulation

Abstract: The cardiovascular effects of naloxone 15 microgram/kg following morphine 2.0 mg/kg were studied in closed-chest dogs during light nitrous oxide-halothane anaesthesia. The bolus injection of naloxone caused an increase in heart rate (73%), cardiac output (20%) and mean arterial pressure (20%). Total peripheral resistance was unaffected. LV dP/dt max and LV dP/dt max/IP increased by 25% and 14% respectively, but positive inotropic effects could not be shown when load data, heart rate and the decrease in left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Naloxone administration is generally associated with an increase in heart rate, cardiac output and arterial blood pressure in humans and in dogs, 60 and studies in the latter have shown increased coronary blood flow and myocardial oxygen consumption. 61,62 Initially, studies of the administration of high doses of naloxone to patients with OUD under general anesthesia for purposes of detoxification produced no significant changes in heart rate, mean arterial pressure, cardiac index, peripheral resistance or oxygen saturation. 63 However, later studies found that such treatment with naloxone is accompanied by a 30-fold and 3-fold increase in epinephrine and norepinephrine plasma concentrations respectively, and that this catecholamine surge is associated with significant increases in cardiac index, stroke volume index, heart rate, whole-body oxygen consumption and a systemic vascular resistance index decrease, all consistent with the effect of epinephrine.…”
Section: Opioid Withdrawalmentioning
confidence: 99%
“…Naloxone administration is generally associated with an increase in heart rate, cardiac output and arterial blood pressure in humans and in dogs, 60 and studies in the latter have shown increased coronary blood flow and myocardial oxygen consumption. 61,62 Initially, studies of the administration of high doses of naloxone to patients with OUD under general anesthesia for purposes of detoxification produced no significant changes in heart rate, mean arterial pressure, cardiac index, peripheral resistance or oxygen saturation. 63 However, later studies found that such treatment with naloxone is accompanied by a 30-fold and 3-fold increase in epinephrine and norepinephrine plasma concentrations respectively, and that this catecholamine surge is associated with significant increases in cardiac index, stroke volume index, heart rate, whole-body oxygen consumption and a systemic vascular resistance index decrease, all consistent with the effect of epinephrine.…”
Section: Opioid Withdrawalmentioning
confidence: 99%
“…Dosing of naloxone for opioid overdose remains an area of continued debate in human medicine. There have been several experimental studies involving opioid reversal with naloxone in dogs using various doses 26–28 . In one such study, a dose of 0.01 mg/kg IV or 0.04 mg/kg IM temporarily reversed most of the effects of oxymorphone 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several experimental studies involving opioid reversal with naloxone in dogs using various doses. [26][27][28] In one such study, a dose of 0.01 mg/kg IV or 0.04 mg/kg IM temporarily reversed most of the effects of oxymorphone. 28 The suggestion is to begin with a 0.01 mg/kg intravenous bolus and repeat every 2 minutes at increased doses, up to a maximum dose of 15 mg, 10,25 which would be 37.5 mL of the 0.4 mg/mL solution.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 99%
“…An acute abstinence syndrome can appear when reversal takes place so abruptly, accompanied by a metabolic stimulation directly proportional to the dose of opiate used, to the interval which precedes the reversal, to the dose of antagonist used, to the speed of antagonist administration, and to the rapidity of its antagonist action (De Castro, 1976). For example, a serious imbalance between myocardial oxygen requirement and available oxygen (MVO2 demand/MO2 supply) Premedication Pure analgesic anaesthesia Potentialised analgesic anaesthesia General anaesthesia; "balanced anaesthesia" Analgosedation Complement to local -regional anaesthesia Post-operative analgesia Acute pain Chronic pain Unwanted overdosage Deliberate overdosage: in obstetrics Sequential analgesic anaesthesia Potentialised analgesic anaesthesia can result in ischemia in coronary patients (Patschke, 1977).…”
Section: Antagonist Properties Of Narcotic Antagonistsmentioning
confidence: 99%